Combating coloniality: the cultural policy of post-colonialism. Issue 3 (4th May 2017) - Mulcahy, Kevin V.
Abstract : The distinguishing characteristic of cultural policy in countries characterized by a legacy of coloniality is the importance of the identity formation and the politics that are involved in formulating its definition. At root, coloniality is an experience involving dominating influence by a stronger power over a subject state. However, this is not just a matter of external governance or economic dependency, but of a cultural dominance that creates an asymmetrical relationship between the 'center' and the 'periphery, ' between the ruling 'hegemon' and the marginalized 'other.' In these circumstances, what constitutes an "authentic" culture, and how this informs national identity, is a central political and social concern.